ESL, EFL, and bilingual education : exploring historical, sociocultural, linguistic, and instructional foundations - Zimmerman, Lynn W. (Research in bilingual education., 2010)
This collection of essays examines the historical, social, cultural, and educational foundations of ESL/EFL/Bilingual Education. The four themes of this book are:· Historical, Legal and Political Foundations of Bilingual/ESL Education· Linguistic and Sociocultural Issues in ESL/EFL Education· Educational Reform and English Language Teaching· Effectively Teaching Bilingual/ESL/EFL StudentsThis volume offers a concise overview of English language learning issues from foundations to current reform to practical guidelines to implement in the classroom. The articles are a variety of theoretical essays, reports of research and practical guides to teaching ESL/EFL/bilingual populations. Many of the essays are presented from the perspective of critical pedagogy relying on the work of educational theorists such as Paulo Freire, Lisa Delpit, and Michael Apple. Although there are connections among the essays, this collection allows the reader to read any of the essays as individual pieces, so the reader can focus on the issues that are most relevant.This book is aimed at instructors of ESL/EFL/bilingual foundations courses. It would be appropriate for undergraduate or graduate level courses. There is some international appeal for this text since several of the essays focus on general English language learning issues, and at least two focus on international issues.